Distance Deception by Fragmented Objects: How Figures May Alter the Perceived Depth of the Background. (March 2022) - Roncato, Sergio
Illusory displacements in depth may be perceived in simple geometric configurations devoid of cues for spatial computation but also in real-world images where there is no shortage of information of this kind. Two of these different contexts drew the attention of vision scientists as sources of depth illusions: the Kanizsa square and the images of statues that Catalano's created with a part missing. Similar depth alterations occur in both cases: the portions of the background surrounded by "inducers" (pacmen or body parts) are perceived as coming to the foreground. These illusory effects appear more vivid and diverse in the real-world context leading to hypothesize an involvement of the figural complexity in the misperception. A check was carried out by testing the effects of the background articulation on the depth perception of the illusory Kanizsa square. It was confirmed that both background and inducers articulation enhance the phenomenon. A large set of Catalano's images was analyzed, looking for basic distorting sources along the torn contours. Several basic factors were found, but not enough to account for the complexity of this variegated, often paradoxical phenomenon.